Bleaching sensitivity with a desensitizing in-office bleaching gel: a randomized ﻿double-blind clinical trial - Maran, Bianca Medeiros; Vochikovski, Laína; Hortkoff, Diego Rafael de Andrade; Stanislawczuk, Rodrigo; Loguercio, Alessandro D; Reis, Alessandra (Quintessence international (Berlin, Germany : 1985), 2020)
This split-mouth study assessed the bleaching sensitivity (risk and intensity) and color change after in-office bleaching using a desensitizing-containing (5% potassium nitrate) and a desensitizing-free 35% hydrogen peroxide gel. The null hypothesis was that there would be no differences between study groups regarding bleaching sensitivity. Sixty patients participated in this split-mouth study. The subjects received desensitizing-containing hydrogen peroxide in half of the maxillary arch, and the other half received a desensitizing-free hydrogen peroxide, defined by random sequence, in two dental bleaching sessions. The bleaching sensitivity was evaluated during bleaching and from 1 h to 48 h after each bleaching session using a visual analog scale and numeric rating scale; the McNemar test, the Wilcoxon signed-rank test, and the Student-Newman-Keuls test were used for statistical analysis. The color was measured at baseline and 30 days post-bleaching, evaluated with paired t tests (P = .05). Statistically similar risks of bleaching sensitivity were observed (P = 1.000), but the intensity of bleaching sensitivity was lower (P < .011) on average by 1.32 visual analog scale units in the group bleached with the desensitizer-containing gel during up to 24 h assessment times. No statistical difference in color change was observed between groups (P > .321). The incorporation of 5% potassium nitrate into in-office bleaching gels does not reduce the risk of bleaching sensitivity, but it reduces its intensity slightly without jeopardizing color change.